Wheel‐Shape Heterometallic Ti10M2‐oxo Clusters (M = Ni, Co) with Effective Visible Light Absorption. Issue 3 (26th January 2019) - Liu, Xiao‐Xue; Fang, Wei‐Hui; Chen, Shumei; Zhang, Lei; Zhang, Jian
Summary of main observation and conclusion: In order to make visible light harvest crystalline polyoxo‐titanium clusters, we initially used transition metal pivalate complexes in this system and prepared successfully two isostructural compounds, [Ti10 M2 (PPO)4 (μ3 ‐O)8 (μ2 ‐O)4 (PA)12 (MeCN)4 ]·4HPA (PPOA = phenylphosphonic acid, HPA = propionic acid, M = Ni, PTC‐52‐Ni; M = CoPTC‐52‐Co ). Single‐crystal X‐ray diffraction study showed that these two complexes possessed wheel‐shape heterometallic Ti10 M2 ‐oxo clusters. The absorption bands of these two compounds shift effectively toward the visible‐light region. Furthermore, their photocurrent response has also been studied. Abstract : Herein, we report the synthesis and structures of two wheel‐shape heterometallic Ti10 M2 ‐oxo clusters (M = Ni, Co). The absorption bands of these two compounds shift effectively toward the visible‐light region.